Multiple Koenen Tumors, a Rare Entity: Combination Treatment with 1% Topical Sirolimus Electrofulguration and Excision - Viswanath, Vishalakshi (Skin Appendage Disord, 2021)
INTRODUCTION: Koenen tumors are benign, cutaneous manifestations of tuberous sclerosis. These are disfiguring, painful, and challenging to treat as they frequently recur. We report a case of long-standing, multiple Koenen tumors affecting all twenty nails in an elderly female who was successfully treated with a combination of topical sirolimus 1%, surgical excision, and electrofulguration. CASE REPORT: A 57-year-old lady presented with multiple, asymptomatic periungual, and subungual tumors affecting all twenty nails since 27 years. Cutaneous examination revealed confetti macules, ash-leaf macule, and shagreen patch over trunk. Nail biopsy was compatible with Koenen's tumor. Computerized tomography of brain showed diffuse patchy sclerosis. The tumors were treated with topical sirolimus 1% ointment for 10 months with excellent regression. Electrofulguration for both great toenails and surgical excision of right thumbnail periungual fibroma was done. 1% sirolimus was advised after the surgical treatment. There were no adverse effects or recurrence of tumors over a 2-year follow-up. DISCUSSION: Topical sirolimus 1% was effective in tumor regression and preventing new tumor formation. Larger tumors that interfered in daily chores were treated with excision and electrofulguration. Thus, a combination treatment for this rare presentation of tuberous sclerosis provided optimum results.